Decoupled current control and sensor fault detection with second‐order sliding mode for induction motor. Issue 4 (1st February 2015) - Kommuri, Suneel Kumar; Rath, Jagat Jyoti; Veluvolu, Kalyana Chakravarthy; Defoort, Michael; Soh, Yeng Chai
Abstract : This study proposes a new decoupled control method for induction motor (IM) based on higher order sliding mode (HOSM) controller. The proposed controller serves dual purpose by offering decoupled control and sensor fault detection. In this scheme, the decoupled control of d − q currents does not require the knowledge of the speed. The HOSM controllers play the same role as the compensation voltages produced by a decoupling compensator. From the compensation voltages, the speed can be estimated accurately through algebraic calculations. The estimated and actual speeds are then employed for fault detection algorithm to detect the fault. Simulations on a 1/4‐hp three‐phase IM in the presence of random measurement noise highlights the performance of the proposed approach for decoupling current control and robust sensor fault detection.